If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6t + 16 = 9 Reorder the terms: 16 + 6t = 9 Solving 16 + 6t = 9 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 6t = 9 + -16 Combine like terms: 16 + -16 = 0 0 + 6t = 9 + -16 6t = 9 + -16 Combine like terms: 9 + -16 = -7 6t = -7 Divide each side by '6'. t = -1.166666667 Simplifying t = -1.166666667
| 1/5/1 | | (3/4)t+(1/8)=(3/4)(t+8) | | m/4=9/5 | | -1/5/-1 | | 6+16=9 | | 20=-2v | | -2x=-2+5 | | 0=-6n-2n | | 2x+9-2=31 | | 4.4x+64=19.36+8x | | x+(3x^1/2)-10 | | 2+6d-4= | | 9/11*14.4=-12 | | 4(x+2)-6=2x | | -4=6b-4+2b | | 9/2d=27 | | m/4=h/24 | | s+2/1/2s+10=31 | | 9(2/3) | | -x-24=-8 | | 20+5n=6n-3(n-4) | | (x^7z^5)/(x^6z) | | a-4/5=14 | | 7/15x/-1/5=4 | | 6/7(84+35y) | | 6r+-1s+9r+-3s= | | x/2+22=10 | | y-1/x=-3/4 | | 5x+20=10y | | 2x-(4x-6)=6x+38 | | 4y+12=-1/3(8-12y) | | 9/11*14.4 |